1989
DOI: 10.1177/001698628903300102
|View full text |Cite
|
Sign up to set email alerts
|

A Special Program for Highly Able Rural Youth in Grades Five and Six

Abstract: There are many barriers to appropriate programming for highly gifted students in rural schools. This paper describes an attempt to overcome these barriers. Twp New York State County Boards of Cooperative Services (B.O.C E.S.) cooperated to begin a program for 32 fifth and sixth grade academically advanced students from 19 schools covering 2600 square miles. The local schools sent students one full day a week to one of five sites for advanced level study in humanities and science.Objective and subjective evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Goldring (1990) concluded that there were no differences in self-concept for students in separate classes when compared with those in regular classes. Likewise, Vaughn et al (1991), Aldrich and Mills (1989), and Van Tassel-Baska et al (1989) found similar results for their analyses of students in pullout programs.…”
Section: Research On Affective Outcomessupporting
confidence: 53%
“…Goldring (1990) concluded that there were no differences in self-concept for students in separate classes when compared with those in regular classes. Likewise, Vaughn et al (1991), Aldrich and Mills (1989), and Van Tassel-Baska et al (1989) found similar results for their analyses of students in pullout programs.…”
Section: Research On Affective Outcomessupporting
confidence: 53%
“…Goldring (1990) concluded that self-perception did not differ between students in separate classes and students in regular classes. Similar results were found in some studies of students in pull-out programs (Aldrich and Mills, 1989; VanTassel-Baska et al, 1989; Vaughn et al, 1991). However, in another study, students in a pull-out program were found to have significantly higher mean self-perception scores relative to their elementary and middle school counterparts (Feldhusen et al, 1990).…”
Section: Review Of the Literaturesupporting
confidence: 90%
“…By contrast, other studies found that students in a gifted program exhibited greater academic performance than did gifted students not enrolled in such a program (Aldrich and Mills, 1989; Reis et al, 1993; Roberts, Ingram, and Harris, 1992). However, self-perception did not differ between treatment and control students in one study (Lynch and Mills, 1990).…”
Section: Review Of the Literaturementioning
confidence: 71%
“…The limited research using a comparison group and some adjustment for selection bias to study the effects of gifted programming on upper elementary students’ reading and mathematics achievement or attitudes has produced mixed results. For instance, Aldrich and Mills (1989), Delcourt et al (2007), Reis et al (1993), and Roberts, Ingram, and Harris (1992) found higher achievement for students in a gifted program compared with other gifted students. In specific content areas, VanTassel-Baska, Zuo, Avery, and Little (2002) and Gavin, Casa, Adelson, Carroll, and Sheffield (2009) found higher literature and mathematics achievement, respectively, when high-end curriculum was used, particularly in self-contained settings.…”
Section: Background Of the Studymentioning
confidence: 98%